2012
DOI: 10.1007/978-3-642-33460-3_27
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Regularized Ensemble Pruning

Abstract: Abstract. Diversity among individual classifiers is recognized to play a key role in ensemble, however, few theoretical properties are known for classification. In this paper, by focusing on the popular ensemble pruning setting (i.e., combining classifier by voting and measuring diversity in pairwise manner), we present a theoretical study on the effect of diversity on the generalization performance of voting in the PAC-learning framework. It is disclosed that the diversity is closely-related to the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 26 publications
(49 reference statements)
3
74
0
Order By: Relevance
“…In particular, it was often limited to the proposed evaluation measure, and using different and incomparable experimental set-up (i.e., different data sets, base classifiers, ensemble construction methods, etc.). We also point out that, among these works, only in [14,24] the use of the proposed evaluation functions provided a statistically significant improvement over a direct estimation of ensemble performance.…”
Section: Aim Of This Workmentioning
confidence: 89%
See 4 more Smart Citations
“…In particular, it was often limited to the proposed evaluation measure, and using different and incomparable experimental set-up (i.e., different data sets, base classifiers, ensemble construction methods, etc.). We also point out that, among these works, only in [14,24] the use of the proposed evaluation functions provided a statistically significant improvement over a direct estimation of ensemble performance.…”
Section: Aim Of This Workmentioning
confidence: 89%
“…A different and theoretically grounded view on the role of diversity in ensemble pruning was proposed in [14], in the context of ensembles of binary classifiers combined by majority voting: using a suitable diversity measure it was shown that promoting diversity can be seen as a regularization technique. A pruning method was also proposed based on these results, which exploits a strategy similar to FS: it starts with the most accurate classifier from the original ensemble, then iteratively sorts the remaining classifiers based on their diversity (evaluated using the proposed measure) with the current sub-ensemble, and among the most diverse ones it selects the classifier which leads to the next most accurate sub-ensemble.…”
Section: Previous Work On Using Diversity For Ensemble Designmentioning
confidence: 99%
See 3 more Smart Citations